2010
DOI: 10.1097/wnn.0b013e3181c5e2d4
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Report of Word-finding and Memory Deficits in Normal Aging and Dementia

Abstract: Objective Compare subjective reports of both memory and word-finding deficits to clinical diagnosis and objective neuropsychological testing. Background With the increasing number of aging individuals with cognitive impairments, effective screening measures would improve the likelihood of detection. Subjective reports of symptoms are typically obtained in clinical settings, yet the validity of these reports is relatively unknown. Methods Clinical screening for dementia was carried out at an Alzheimer’s dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This analysis was conducted with the assumption that some studies that did not screen for MCI may have included some MCI participants in their normatively aging sample. Some research has identified that individuals with MCI are more accurate when making memory judgments (Calley et al, 2010; Cook & Marsiske, 2006). This may be because individuals with MCI recognize that their memory performance has changed over time and they then match their perceptions about their memory to reflect this notion of decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis was conducted with the assumption that some studies that did not screen for MCI may have included some MCI participants in their normatively aging sample. Some research has identified that individuals with MCI are more accurate when making memory judgments (Calley et al, 2010; Cook & Marsiske, 2006). This may be because individuals with MCI recognize that their memory performance has changed over time and they then match their perceptions about their memory to reflect this notion of decline.…”
Section: Discussionmentioning
confidence: 99%
“…making memory judgments (Calley et al, 2010;Cook & Marsiske, 2006). This may be because individuals with MCI recognize that their memory performance has changed over time and they then match their perceptions about their memory to reflect this notion of decline.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Two of the most salient symptoms are word-finding and memory difficulties (see Calley et al 2010). Several studies of the symptoms reported by veterans with Gulf War Illnesses corroborate reports of difficulties with word finding (Fukuda et al 1998; Barrett et al 2002) and/or memory (Pierce 1997;Fukuda et al 1998;Gray et al 2002;Ishøy et al 1999); however, the incidence and prevalence of deficits related to semantic memory with these symptoms, the etiology of the impairments, and the brain regions involved are unknown.…”
Section: Introductionmentioning
confidence: 96%
“…Mouse studies suggest that PP1 functions as a suppressor of learning and memory (Genoux et al 2002). Because defects in learning and memory are among the signs of Alzheimer's disease (Calley et al 2010), a relationship between PP1 and…”
Section: Localization Of Pp1c With Tau In Sam Brainsmentioning
confidence: 99%